Note—Operations Sequencing in Discrete Parts Manufacturing - Bard, Jonathan F.; Feo, Thomas A. (Management Science, 1989)
This paper presents an algorithm for efficiently sequencing the cutting operations associated with the manufacture of discrete parts on a CNC machine. The problem is first modeled as an integer program but recast via Lagrangian relaxation as a min-cut problem on a bipartite network. Tight lower bounds are obtained with a max-flow algorithm. The corresponding solution is used as input to a greedy heuristic which generates “good” feasible points. Given nonconvergence, a branch and bound strategy is used to find the optimal solution.